Five go off to camp - Blyton, Enid (Hodder Children's London, 2001)
Spook trains in the dead of night! And they seem to vanish into thin air - but where do they go? The Famous Five are on to it! But discovery of an unusual underground tunnel system, and a secret train-service, has them puzzled. If they follow the tracks, will they solve the mystery?